2011
DOI: 10.1504/ijbeam.2011.044126
|View full text |Cite
|
Sign up to set email alerts
|

Timeshare brand affiliation impacts

Abstract: Over the past two decades, internationally branded hotel companies have continued their expansion efforts into the vacation ownership/timeshare resort industry. This act of adding timeshare resorts to the parent company's already existing hotel and resort collection entailed strategic decisions that ranged from: market share, portfolio risk management and crossover financial gains. To address the association of this latter relationship, the authors surveyed vacation ownership consumers' overall satisfaction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…So et al [49] found that lack of safety measures with Airbnb had a negative influence on future behavioral intentions. In the timeshare industry, Kaufman et al [50] equated trust, along with credibility and consumer confidence, with the entrance of branded hotel chains. Möhlmann's [27] study of commercial car sharing and P2P accommodations found that trust had a positive influence on satisfaction in both studies.…”
Section: Trustmentioning
confidence: 99%
“…So et al [49] found that lack of safety measures with Airbnb had a negative influence on future behavioral intentions. In the timeshare industry, Kaufman et al [50] equated trust, along with credibility and consumer confidence, with the entrance of branded hotel chains. Möhlmann's [27] study of commercial car sharing and P2P accommodations found that trust had a positive influence on satisfaction in both studies.…”
Section: Trustmentioning
confidence: 99%
“…Most recently, timeshare research has focused on consumer acceptance and marketing opportunities in specific geographic regions. Perhaps this is due to the continued expansion of the segment and presence of global lodging brands (ARDA, 2010; Gregory, 2011; Kaufman et al , 2011) or recent economic improvements (ARDA International Foundation, 2014). Certainly, opportunities for further investigation in this area exist as researchers have recently only investigated Singapore (Chiang, 2011), and Europe (Cortés-Jiménez et al , 2003).…”
Section: The Literaturementioning
confidence: 99%
“…Sparks found consumers expressing concern over the low resale value for timeshare products. One study examined the impact of large branded hotel corporations' entry into the timeshare market [24]. They found that consumers already loyal to hotel companies had an improved perception and loyalty to both the timeshare product and the hotel company as a result of the association.…”
Section: Literature Reviewmentioning
confidence: 99%